Advanced materials and structural engineering proceedings of the International Conference on Advanced Materials and Engineering Structural Technology (ICAMEST 2015), April 25-26, 2015, Qingdao, China - Hu, Jong Wan (CRC Press/Balkema, 2016)
The ICAMEST 2015 Conference covered new developments in advanced materials and engineering structural technology. Applications in civil, mechanical, industrial and material science are covered in this book.